Evaluation of Whey Protein Wafer Supplementation on The Performance and Blood Profile of Weaning Sheep - Dwi Prasetyoningrum, Widya; Retnani, Yuli; Sujarnoko, Tekad Urip (ANIMAL PRODUCTION, 2025)
The provision of feeder sheep is a problem for farmers due to a high mortality rate among pre- and post-weaned lambs. Whey protein contains amino acids, glucose, and immunoglobulin which facilitate immunity enhancement and body weight gain. This study aimed to evaluate the effectiveness of supplementing whey protein wafer on the performance and profile of weaning sheep. A total of 12 ewe were randomly allotted to 3 treatments: P0 (non-supplemented feed); P1 (1.5% whey protein wafer supplement; and P2 (3% whey protein wafer supplement). Each treatment was replicated four times. The results showed that the whey protein wafer supplement treatment significantly (P<0.05) affected erythrocytes, leukocytes, monocytes, glucose, and cholesterol. Wafer with 3% whey protein supplement showed the best average daily gain, a normal range of blood profile, and a good performance compared to other treatments. The normal blood profiles reflect the sound health of the sheep.